PENGARUH LKS BERBASIS REASONING AND PROBLEM SOLVING TERHADAP HASIL PEMBELAJARAN FISIKA SMAN 1 LUBUK ALUNG KELAS XI SEMESTER 1 - Muzi Novriyani (Universitas Negeri Padang, 2014)
The purpose of this research is to detection of the worksheet effect based reasoning and problem solving to physic learning outcomes of 11 th grade student in SMAN 1 Lubuk Alung. The research of type is quasi exsperiment research and design is randomize control group only design. In this research, 11 th grade students of SMAN 1 Lubuk Alung in academic 2013/2014 as population . The take of sampel was done with clutser random sampling technic. The research of data was learning outcome is three domains. They were cognitive, psikomotor and afective. The data was analyzed with mean equality test at significance level 5%. Outcome of research conclude that there effect was worksheet based reasoning and problem solving give significance to learning outcome of 11th grade students in SMAN 1 Lubuk Alung for cognitive, psikomotor and affective domains at significance level 5%